2013
DOI: 10.1007/s40261-013-0155-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Adding Dapagliflozin to Insulin for the Treatment of Type 2 Diabetes Mellitus in the Netherlands

Abstract: Dapagliflozin in combination with insulin was estimated to be a cost-effective treatment option for patients with T2DM whose insulin treatment regimen does not provide adequate glycaemic control in a Dutch healthcare setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
0
40
1
1
Order By: Relevance
“…Similarly, in a UK population of patients on metformin, the addition of DAPA was shown to be a cost‐effective treatment option, particularly because of the positive effect on weight loss, compared with the addition of a DPP‐4 inhibitor . DAPA was also found to be cost‐effective, reducing the overall incidence of macrovascular and microvascular complications and increasing life expectancy in patients who added DAPA to insulin compared with those on insulin alone . A recently conducted study in a Swedish population found new users of DAPA had lower hospital costs and a lower risk of all‐cause mortality compared with users of DPP‐4 inhibitors, but similar overall costs ($6042 vs. $6363; P = 0.128).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in a UK population of patients on metformin, the addition of DAPA was shown to be a cost‐effective treatment option, particularly because of the positive effect on weight loss, compared with the addition of a DPP‐4 inhibitor . DAPA was also found to be cost‐effective, reducing the overall incidence of macrovascular and microvascular complications and increasing life expectancy in patients who added DAPA to insulin compared with those on insulin alone . A recently conducted study in a Swedish population found new users of DAPA had lower hospital costs and a lower risk of all‐cause mortality compared with users of DPP‐4 inhibitors, but similar overall costs ($6042 vs. $6363; P = 0.128).…”
Section: Discussionmentioning
confidence: 98%
“…This study aimed to assess the long‐term health economic consequences of dapagliflozin versus sulfonylurea, as an add‐on to metformin, from the perspective of the UK NHS. Assessments of the cost‐effectiveness of dapagliflozin versus other antidiabetes agents used as an add‐on to metformin, and in indications other than an add‐on to metformin and settings other than the UK have been presented elsewhere .…”
Section: Introductionmentioning
confidence: 99%
“…When added to metformin, dapagliflozin was reported to be a cost-effective treatment option compared with dipeptidyl peptidase-4 inhibitors, sulphonylureas or thiazolidinediones in patients inadequately controlled on metformin alone [25,100102]. Moreover, dapagliflozin in combination with insulin was also estimated to be a cost-effective treatment for patients who failed to get adequate glycaemic control with insulin alone [103]. These studies confirmed the beneficial profile of dapagliflozin for treating T2DM.…”
Section: Discussionmentioning
confidence: 86%